Effect of Carbon Ion Radiation Induces Bystander Effect on Metastasis of A549 Cells and Metabonomic Correlation Analysis - Yang, Zhen; Zhang, Qiuning; Luo, Hongtao; Shao, Lihua; Liu, Ruifeng; Kong, Yarong; Zhao, Xueshan; Geng, Yichao; Li, Chengcheng; Wang, Xiaohu (Frontiers in Oncology, 2021)
Objective To analyze the effect of carbon ion (12C6+) radiation induce bystander effect on A549 cell metastasis and metabonomics. Methods A549 cell was irradiated with carbon ion to establish the clone survival model and the transwell matrix assay was applied to measure the effect of carbon ion on cell viability, migration, and invasion, respectively. Normal human embryonic lung fibroblasts (WI-38) were irradiated with carbon ions of 0 and 2Gy and then transferred to A549 cell co-culture medium for 24 hours. The migration and invasion of A549 cells were detected by the Transwell chamber. Analysis of metabonomic information in transfer medium by liquid phase mass spectrometry (LC-MS), The differential molecules were obtained by PCA analysis, and the target proteins of significant differences （p<0.001）btained by combining with the STICH database. KEGG pathway was used to analyze the enrichment of the target protein pathway. Results Compared with 0Gy, the colony formation, migration, and invasion of A549 cells were significantly inhibited by carbon ion 2 and 4Gy irradiation, while the inhibitory effect was not significant after 1Gy irradiation. Compared with 0 Gy, the culture medium 24 h after carbon ion 2 Gy irradiation significantly inhibited the metastasis of tumor cells (p<0.05). LC-MS analysis showed that 23 differential metabolites were obtained in the cell culture medium 24 h after carbon ion 0 and 2Gy irradiation (9 up-regulated and 14 down-regulated). Among them, 2 were up-regulated and 2 down-regulated (p<0.001). 41 target proteins were corresponding to these four differential molecules. Through the analysis of the KEGG signal pathway, it was found that these target molecules were mainly enriched in Purine metabolism, Tyrosine metabolism, Cysteine and methionine metabolism, Peroxisome, and Carbon metabolism; Neuroactive ligand-receptor interaction, Calcium signaling pathway, Arachidonic acid metabolism, and Fc epsilon RI signaling pathway. Conclusion The bystander effect induced by 2Gy carbon ion radiation inhibits the metastasis of tumor cells, which may be that carbon ions change the metabolites of irradiated cells, so that indirectly affect the metabolism of tumor cell growth microenvironment, thus inhibit the metastasis of malignant tumor cells.